The Role of Endothelial Progenitor Cells in Acute Kidney Injury - Becherucci, Francesca; Mazzinghi, Benedetta; Ronconi, Elisa; Peired, Anna; Lazzeri, Elena; Sagrinati, Costanza; Romagnani, Paola; Lasagni, Laura (Blood purification, 2009)
Acute kidney injury (AKI) is characterized by a sudden impairment of kidney function, which results in the retention of urea and other nitrogenous waste products and in the perturbation of extracellular fluid volume as well as electrolyte and acid-base homeostasis. The dysfunction and apoptosis of tubular epithelial cells are of key importance for the pathophysiological consequences of AKI. However, a growing body of evidence supports the contribution of altered renal vascular structure and function in potentially initiating and extending the initial tubular injury. Vascular injury and dysfunction result in alterations of renal oxygenation and hemodynamics that may have long-term effects in regards to renal function, predisposing to chronic kidney disease. There is growing evidence that endothelial progenitor cells (EPCs) may improve vascular regeneration in different ischemic organs, and recent data suggest that EPCs are mobilized after acute renal ischemia and recruited in ischemic kidney areas and can ameliorate AKI through both paracrine effects and repair of injured microvasculature. The loss of endothelial cell function may represent an important therapeutic target, in which EPCs may show potential importance in ameliorating the acute and chronic effects of ischemic AKI.